Trust institutions, perceptions of economic performance and the mitigating role of political diversity - Samba Diop; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
Several previous studies have explored the nexus between trust and socio-economic conditions but do not attempt to examine channels through which the relation operates. In this paper, we examine how political fractionalization mitigates the positive relationship between trust institutions and national economic performance in Africa. Using Round 7 data of Afrobarometer in over 1000 districts in 34 countries, we find that trust institutions positively and significantly affect economic performance. Nevertheless, the positive effect is attenuated in districts with a high level of political diversity. More specifically, a higher level of trust is associated with lower economic performance at a higher level of political fractionalization and vice versa, with a steady linear decrease of the estimated coefficients. Policy implications are discussed.
Keywords: K00; O10; P16; P43; P50; 330; Trust institutions; economic performance; political diversity